Nonobstetric anesthesia during pregnancy. Issue 3 (June 2016) - Heesen, Michael; Klimek, Markus
Abstract : Purpose of review: Nonobstetric anesthesia during pregnancy is challenging – not only for the anesthetist. Owing to the difficulties of ethical consent for randomized studies in this special patient group, the available evidence is quite low. Nevertheless, recently several guidelines for the management of pregnant patients undergoing nonobstetric anesthesia have been published. We review the current guidelines developed under the auspices of the Society of American Gastrointestinal Endoscopic Surgeons, guidelines for the management of difficult and failed tracheal intubation in obstetrics, as well as guidelines for the management of a pregnant trauma patient. Recent findings: The algorithms for management of the difficult airway during pregnancy should be made available in every institution that cares for pregnant women. During laparoscopic surgery strict limitation of the pneumoperitoneal pressure to avoid maternal hypercapnia and fetal acidosis is strongly recommended. An injured pregnant woman should be transferred to a maternity facility when the injury is not life or limb threatening. In case of major trauma, stabilization and care of the woman is priority. Summary: Several guidelines with high relevance for the care of pregnant women undergoing nonobstetric surgery have been published. Although the level of evidence may be low they can probably contribute to an improvement in the care and outcome of this patient group.